The technique of using balls of different weights and diameters for the interrelated development of physical qualities, accuracy of strikes and psychophysiological capabilities of young football players - O.G. Kanishchev; Zh.L. Kozina; V.M. Grynyova; V.V. Masych (H.S. Skovoroda Kharkiv National Pedagogical University, 2021)
Aim: determination of the influence of the technique of using balls of different weights and diameters on the level and structure of psychophysiological indicators, physical and technical fitness of football players at the initial stage of training. Material and methods. The study was attended by 22 young footballers 10-12 years old. The subjects were divided into two groups (control and experimental) for 11 people in each. The control and experimental group trained the same amount of time for the same progips, but in the experimental group, in the main part of the class, used the technique of complex development of precision-target movements. Measured the level of physical and technical preparedness, as well as the level of psychophysiological functions of athletes. Results. It is shown that the experimental group experienced significant improvements in the techniques of football due to the development of precision-oriented skills. Really improved results of physical and technical preparedness of athletes of the experimental group were revealed. The control group is also characterized by a significant improvement in testing results by level of technical and physical fitness, but not reliable or at a lower level of significance. The positive influence of the method of complex development of precision-target movements on the psychophysiological indices of athletes is shown. It was shown that after the experiment, the number of reliable interrelationships between the indicators of psychophysiological functions and the indicators of technical and physical fitness in the experimental group increased, and in the control remained unchanged. Conclusions. The application of the experimental methodology for the development of precision-target movements positively influenced the level of technical and physical preparedness, psycho-physiological indicators, as well as the structure of the complex preparedness of athletes.